Pengembangan Sistem Informasi Perpustakaan Berbasis Web Pada Perpustakaan Kecamatan Bungah - Nurur Rohmah; Himawat Aryadita; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Bungah District Library has problems in data management and efficiency of loaning and returning services by library staff. The complexity of library collections, library visitors data, and loan transactions demand the need of information technology to automate business processes in Bungah District Library. This study aims to build a web-based library information system that can help manage data and improve the quality of service loan transactions at the library. The software development method that used in this study is the waterfall method, which at the design and implementation stage applies the design pattern of model view controller or MVC pattern. While at the testing stage conducted sequentially from unit testing, integration testing, validation testing, reliability testing, compatibility testing, and acceptance testing. Unit tests using basis path technique shows that system has simple structure, easy to understand and implemented. Integration tests using white box method shows valid result. Validation tests using black box method shows that 26 functions of system can work properly. Reliability tests using nelson calculation shows that the system can run consistently. Compatibility testing result shows that the system can be used well on 6 types of browser. And the result of acceptance testing shows that all of functions can run well and accepted by stakeholder.